2012
DOI: 10.1093/hmg/dds373
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association analysis of genetic generalized epilepsies implicates susceptibility loci at 1q43, 2p16.1, 2q22.3 and 17q21.32

Abstract: Genetic generalized epilepsies (GGEs) have a lifetime prevalence of 0.3% and account for 20-30% of all epilepsies. Despite their high heritability of 80%, the genetic factors predisposing to GGEs remain elusive. To identify susceptibility variants shared across common GGE syndromes, we carried out a two-stage genome-wide association study (GWAS) including 3020 patients with GGEs and 3954 controls of European ancestry. To dissect out syndrome-related variants, we also explored two distinct GGE subgroups compris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(94 citation statements)
references
References 59 publications
(61 reference statements)
5
86
1
Order By: Relevance
“…One GWAS on idiopathic epilepsy did show evidence for association at four separate loci (1q43, 2p16.1, 2q22.3, and 17q21.32). However, as has been the pattern in other diseases, the results suggested that the alleles discovered accounted for a very small portion of the relative risk [67]. (Of note, none of the genes of interest mentioned were channel genes.)…”
Section: Genome-wide Association Studies Of Common Epilepsymentioning
confidence: 73%
“…One GWAS on idiopathic epilepsy did show evidence for association at four separate loci (1q43, 2p16.1, 2q22.3, and 17q21.32). However, as has been the pattern in other diseases, the results suggested that the alleles discovered accounted for a very small portion of the relative risk [67]. (Of note, none of the genes of interest mentioned were channel genes.)…”
Section: Genome-wide Association Studies Of Common Epilepsymentioning
confidence: 73%
“…In our study, neuroblastoma SH-SY5Y cell viability was reduced by pathogenic HttQ103-GFP expression, and VRK2 overexpression increased HttQ103-GFP aggregate formation in SH-SY5Y cells, suggesting that the level of active VRK2 in neuronal cells may be important for the onset and progression of polyQ diseases. Moreover, genome-wide association studies have revealed that VRK2 has emerged as one of the risk factors against neurological disorders, including schizophrenia (43,44) and epilepsy (45,46). VRK2 expression, however, is known to be much higher in actively proliferating cells and is maintained at a low level in the brain (47).…”
Section: Discussionmentioning
confidence: 99%
“…The selected SNPs are located within genes which encode sodium ion channel SCN1A (rs1685381 and rs8191987), SCN8A (rs303778), SCN3B (rs1783901), potassium ion channel KCNQ2 (rs1801545), KCNAB1 (rs992353), and glutamate receptor GRM4 (rs4711374, rs1466650, rs937039, rs2499697, rs2451357, rs9380405, rs745501, rs11753413, rs2451334, and rs2029461). Furthermore, 10 additional loci including VRK2 (rs13026414), COPZ2 (rs72823592), ZEB2 (rs10496964), CHRM3 (rs12059546), SCN1A (rs11890028), PCDH7 (rs28498976 and rs1044352), GOLIM4 (rs111577701), GABRA2 (rs535066), and MMP8 (rs1939012), found to be associated with epilepsy in GWAS, were included in the study [Steffens et al, 2012 …”
Section: Selection Of Snpsmentioning
confidence: 99%
“…Recently conducted genome-wide association studies (GWAS) and meta-analyses facilitated the identification of new loci associated with the risk of epilepsy, both in the genes encoding ion channels and the genes unrelated to "channelopathies" [Steffens et al, 2012; International League against Epilepsy Consortium on Complex Epilepsies, 2014].…”
Section: Introductionmentioning
confidence: 99%